2010
DOI: 10.1029/2009jd012799
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of outgoing longwave radiation from Atmospheric Infrared Sounder radiance measurements

Abstract: This study demonstrates the ability to use Atmospheric Infrared Sounder (AIRS) hyperspectral radiance measurements and collocated Clouds and the Earth's Radiant Energy System outgoing longwave fluxes to estimate top‐of‐atmosphere outgoing longwave radiation (OLR) from AIRS radiance measurements. The first 35 principal component scores of AIRS radiances from its 1707 pristine channels are used as predictors, and the regression coefficients are generated in eight regimes of AIRS view angle to account for angular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…To evaluate CrIS OLR products, the package utilizes an approach that uses the Aqua CERES OLR as the absolute reference and the Aqua AIRS OLR as the third transfer. Previous analyses of Aqua CERES and AIRS OLR have shown that they are stable over the time period of this study [13,14], and are therefore suitable for our validation analysis. Included in our validation analysis are the two CrIS OLR products evaluated with the NUCAPS: the SNPP CrIS OLR and the NOAA-20 CrIS OLR.…”
Section: Validation Methods and Datasetsmentioning
confidence: 79%
See 2 more Smart Citations
“…To evaluate CrIS OLR products, the package utilizes an approach that uses the Aqua CERES OLR as the absolute reference and the Aqua AIRS OLR as the third transfer. Previous analyses of Aqua CERES and AIRS OLR have shown that they are stable over the time period of this study [13,14], and are therefore suitable for our validation analysis. Included in our validation analysis are the two CrIS OLR products evaluated with the NUCAPS: the SNPP CrIS OLR and the NOAA-20 CrIS OLR.…”
Section: Validation Methods and Datasetsmentioning
confidence: 79%
“…Satellite OLR products are generated mainly from broadband [6][7][8][9], multispectral [10,11], and hyperspectral datasets [12][13][14]. The Clouds and Earth's Radiant Energy System (CERES) instruments are examples of broadband sensors that directly measure reflected solar radiation and Earth-emitted radiation from TOA to the surface, thus providing records of spatial and temporal variations of ERB components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show a mean difference of 0.3 W/m 2 from CERES with a standard deviation of 2.7 W/m 2 . These results indicate that AIRS can be used to monitor CERES and serve as a backup in the event of failure 16 , but more importantly, the AIRS provides attribution of the observed OLR to changes in geophysical variables such as temperature profile, water vapor profile and dust aerosols.…”
Section: Climate Processes and Model Validationmentioning
confidence: 92%
“…As a result, the Clouds and Earth Radiant Energy System (CERES) sensor was designed to provide radiation fluxes at the surface and at levels throughout the atmosphere and to investigate the cloud‐radiation feedback on the Earth's climate system (Wielicki et al , 1996; Loeb et al , 2001; Geier et al , 2003). Huang et al (2008) and Sun et al (2010) used collocated AIRS hyperspectral radiance measurements and CERES outgoing long wave fluxes to estimate TOA OLR from AIRS radiance measurements.…”
Section: Meteorological Parametersmentioning
confidence: 99%